(untitled) (Educational Dimension, 2021)
An analysis of the traditional methodology for the implementation of laboratory work “Measurement of acceleration in uniformly accelerated movement” in 10 classes is carried out and its disadvantages has been identified. The author’s methodology of execution of this laboratory work is considered, which eliminates the detected shortcomings on the “standard” levels and “in-depth”. In addition to the main experiment, this is necessarily for all students, an additional experiment is proposed, as well as an additional experimental task that allows you to prove that it is really equipped with movement and recycle relevant moving graphics and speeds from time to time. The student’s conclusion, control issues are created to justify measures to reduce the experiment error. Laboratory work is designed in the form of a copybook with a printed base. Planned methods for improving the methodology of performing laboratory work using the last platform of Arduino in STEM technologies.